Ex Vivo Treatment with a Polyphenol-Enriched Cocoa Extract Ameliorates Myocardial Infarct and Postischemic Mitochondrial Injury in Normotensive and Hypertensive Rats - González Arbeláez, Luisa Fernanda (2016)
Our objective was to determine the effects of a polyphenol-enriched cocoa extract (PCE) on myocardial postischemic alterations in normotensive (Wistar rats, W) and spontaneously hypertensive rats (SHR). Isolated hearts were submitted to 110 min of perfusion or 20 min stabilization, 30 min global ischemia, and 60 min reperfusion (R). Other hearts were treated with PCE at the onset of R. Infarct size, the reduced glutathione (GSH), and the expression of phospho-Akt, P-GSK-3β, and P-eNOS were assessed. In isolated mitochondria, the Ca2+-mediated response of mitochondrial permeability transition pore (mPTP), membrane potential (δψm), and superoxide production were determined. PCE decreased infarct size, partly preserved GSH, increased the P-Akt, P-GSK-3β, and P-eNOS contents, improved mPTP response to Ca2+, decreased the superoxide production, and restored δψm. These data show that PCE decreases the cardiac postischemic damage in W rats and SHR and suggest that Akt/GSK-3β/eNOS dependent pathways are involved.